Pelatihan Penelitian Tindakan Kelas kepada Para Pendidik MTs dan MA - Nur Apriany Nukuhaly; Syafrudin Kaliky; Gamar Assagaf; Patma Sopamena; Hilaluddin Hanafi (IAIN AMBON, 2022)
This Class Action Research Workshop (PTK) aims to train educators of MTs N 4 Central Maluku and MA N 3 Central Maluku to reflect on the results obtained from the learning process that has been carried out previously in the form of scientific papers. This devotion to educators uses the method of training and workshops. The participants in this activity were educators at MTs N 4 Central Maluku and MA N 3 Central Maluku which totaled 50 people. The result of this training and workshop is that participants have been able to create a class action research design and know-how to carry out the process and report on class action research.